Evaluation of reactive Si and Al amounts in various geopolymer precursors by a simple method. (March 2019) - Buruberri, L.H.; Tobaldi, D.M.; Caetano, A.; Seabra, M.P.; Labrincha, J.A.
Abstract: The soluble amount of Si and Al in biomass fly ash (BFA) and metakaolin (MK) was determined by using a spectrophotometric (colorimetric) method. This low-cost technique is simple to operate, and shows high selectivity and suitable sensitivity. Molybdenum blue and eriochrome cyanine R (ECR) methods were used to quantify, respectively, the SiO2 and Al2 O3 amounts leached out to a sodium hydroxide solution (10 mol dm –3 ). The obtained results were compared with the chemical composition of the precursors and their amorphous phase amounts. The soluble amount of SiO2 was 7.5 wt% for BFA, and 40.3 wt% for MK. Values equal to 6.3 wt% for BFA and 35.2 wt% for MK were estimated for Al2 O3 . These results are quite comparable with those obtained through the combination of X-ray fluorescence (XRF) and X-ray diffraction (XRD) using fully quantitative phase analysis (FQPA): soluble SiO2 equal to 4.4 wt% for BFA and 46.1 wt% for MK, and soluble Al2 O3 equal to 10.0 wt% for BFA and 35.5 wt% for MK. Then, BFA- and MK-based geopolymers were formulated, taking into account the soluble Si and Al contents estimated by the colorimetric methods, testing three distinct (2.5, 3.3 and 4.5) SiO2 /Al2 O3 molar ratios (RS/A ) and curing times (15, 21 and 28 days). The BFA reaction degree (α) and the compressive strength of the obtained samples were determined to validate the reliability of the spectrophotometric estimations. A linear correlation between the two variables was observed in BFA-based geopolymers for curing times ≥ 21 days. At the same time, MK and BFA based samples formulated with a fixed RS/A, adjusted by adding silica fume, show similar compressive strength values. The use of this spectrometric technique to evaluate the amount of reactive components (Si and Al) in the precursors is an interesting tool for the design of, and to predict the performance of, the cured material. Highlights: Quantification of the soluble amounts of Si and Al in biomass fly ash and metakaolin by a simple method. The spectrophotometric technique as a potential tool to design/predict the performance of the geopolymers. The spectrophotometric technique gives more accurate values of reactive Si and Al amounts than the FRX combined with FQPA. The compressive strength values of the prepared geopolymers confirm the reliability of the spectrophotometric estimations.